Influence of the axial loads of rolling stock on the contact-fatigue life of rails - V. S. Kossov; G. M. Volokhov; O. G. Krasnov; M. N. Ovechnikov; A. L. Protopopov; V. V. Oguenko (Вестник Научно-исследовательского института железнодорожного транспорта, 2018)
Analysis of operational data for defective and highly defective rails showed that up to 25 % is the contact-fatigue defects. In connection with the development of heavy haul traffic on the Russian railways, it is relevant to determine the influence of cars with increased axial loads of 25 and 27 tf on the contact fatigue life of rails. The solution of this problem is set forth in this article. The Brown-Miller model of multi-axial fatigue was used in the calculation. This model is integrated into the Fatigue software system, which is tied to the Marc calculation system through Pat-ran. Since under operating conditions the wheel moves (rolls) along the rail on meandering trajectory, in computer modeling weight coefficients were taken into account that characterize the percentage of wheels in the cross-sectional areas of the rail. Calculations of contact fatigue life took into account the variability of vertical loads from the impact on the track of trains formed from innovative open cars with axial loads of 23.5, 25 and 27 tf under operating conditions, loaded with real loading blocks. According to the analysis of calculated data with an increase in axial loads from 23.5 to 25 tf, it is necessary to expect a decrease in the service life of rails in contact fatigue resistance by 19 %, with a further increase in axle loads of up to 27 tf per 32 %. Considering that the share of freight cars with axial loads of 25 tf does not exceed 15...20 %, then on the routes of its use the service life of rails should be expected to decrease by 3...4 %. The method proposed by the authors for predicting the contact fatigue life of rails with increasing axial loads is advisable to improve in part of the experimental determination of the fatigue and strength characteristics of rail steel from the degree of hardening of the rolling surface, its probabilistic properties and the use of the integral distribution law for vertical forces, taking into account the structure of the freight traffic passing through the section. The work was carried out according to the RFBR project 17-20 01088.